Predicting Climate Change Impacts on Crop Pollinators in Brazil - Giannini Tereza Cristina; Guaraci Duran Cordeiro; Wilian França Costa; André Luiz Acosta; William de Oliveira Sabino; Leonardo Miranda; Vera Lúcia Imperatriz-Fonseca; Antônio Mauro Saraiva (Sociobiology)
Pollinators are critical elements of biodiversity as they participate in the reproduction of plant species. Due to their importance in food production, they are one of the most studied groups of ecosystem service providers globally. However, climate change poses a significant threat to this important service delivered to agriculture. We aim to summarize the main advances in Brazilian research on crop pollinators under climate change in the last years, emphasizing future impact predictions. To analyze the effects of climate change on agricultural pollinators, structured data on pollinators and crop species were organized, which also allowed advances in the structuring of data related to the dependence of Brazilian crops on pollinators, as well as determining the value of the pollination service for agriculture. Studies analyzed here cover the following issues: [1] interaction networks; [2] crop pollinators, crop dependence, and pollination service valuation; and [3] climate change impacts. We also present ten recommendations to foster further initiatives related to crop pollinators under climate change.